2019
DOI: 10.1038/s41467-019-09043-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-quenching NIR-II molecular fluorophores for in vivo high-contrast imaging and pH sensing

Abstract: The contrast and sensitivity of in vivo fluorescence imaging has been revolutionized by molecular fluorophores operating in the second near-infrared window (NIR-II; 1000-1700 nm), but an ongoing challenge is the solvatochromism-caused quenching in aqueous solution for the long-wavelength absorbing fluorophores. Herein, we develop a series of anti-quenching pentamethine cyanine fluorophores that significantly overcome the severe solvatochromism, thus affording stable absorption/emission beyond 1000 nm with up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
388
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(394 citation statements)
references
References 46 publications
6
388
0
Order By: Relevance
“…Currently, there are mainly two methods for the designing of NIR‐II fluorophores: conjugation length enhancement and donor‐acceptor (D‐A) engineering . In the former case, increasing conjugation length can redshift both absorption and emission of the polymethine cyanines (such as IR‐26) to the NIR‐II region, whereas the fluorescence attenuates efficiently due to the solvatochromism‐caused quenching .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are mainly two methods for the designing of NIR‐II fluorophores: conjugation length enhancement and donor‐acceptor (D‐A) engineering . In the former case, increasing conjugation length can redshift both absorption and emission of the polymethine cyanines (such as IR‐26) to the NIR‐II region, whereas the fluorescence attenuates efficiently due to the solvatochromism‐caused quenching .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, small‐molecule‐based NIR‐II dyes offer distinct advantages with regard to potential clinical translation. Therefore, the development of organic small‐molecule fluorophores represents an important, newly emerging and dynamic research field in molecular imaging . In particular, organic fluorophores such as CH1055, which is based on a donor–acceptor–donor structure including a benzobisthiadiazole derivative as the acceptor, demonstrate attractive optical properties (NIR‐II emission spectra, good quantum yield, high photostability) and excellent in vivo performance .…”
Section: Introductionmentioning
confidence: 99%
“…We proceeded to measure NIR‐II emission behavior of IR‐FD, QDs, and an IR‐FD/QDs mixture at >1100, 1100–1300, and >1500 nm windows, respectively, again confirming the nonoverlay of selected probes (Figure 1f). We used an 1% Intralipid solution to simulate tissue to test the penetration depth of the QDs compared with clinically used ICG probe . From the fluorescence images of capillaries filled with QDs or ICG solutions, we observed that the QDs achieved a better penetration depth at 9 mm with signal to background ratio (S/B) of ≈1.26, while ICG at 5 mm had S/B of ≈1.07, providing significant improvement of penetration and contrast with QDs in the NIR‐IIb window (Figure 1g).…”
mentioning
confidence: 97%